Pulling at Both Ends of the String: The Political and Legal Tug in Refugee and Migration Policy in Indonesia - Fakhrirafi Zharfan; Ristina Yudhanti; Dewi Sulistianingsih; Achmad Fahmi Zulfikar; Ngboawaji Daniel Nte; Adnan Ibrahim Sarhan; Ridwan Arifin (Universitas Negeri Semarang, 2025)
This paper analyzes the complex and often contradictory dynamics of refugee and migration policy in Indonesia, framed within the political and legal tug-of-war that shapes human rights protections. As one of Southeast Asia’s key transit and destination countries for refugees and migrants, Indonesia's policy approaches are influenced by both international obligations and domestic political considerations. Despite being a signatory to the 1951 Refugee Convention, Indonesia has not adopted comprehensive national legislation to protect refugees, leaving a gap in the legal framework that often results in ad-hoc, inconsistent practices. This study critically examines the tension between political interests—such as national sovereignty, security concerns, and public opinion—and the legal obligations tied to human rights protections under international law. The research analyzes the roles of domestic political actors, including the government, lawmakers, and civil society, in shaping policies related to refugees and migrants. It also explores the legal frameworks that both constrain and enable state actions regarding asylum seekers, detention, and deportation. Through a review of recent case studies and policy shifts, this paper highlights the challenges of balancing humanitarian obligations with domestic priorities. The analysis underscores the need for a more coherent and rights-based approach to migration and refugee policy in Indonesia, suggesting that the existing legal and political landscape often pulls in opposite directions, undermining effective protection for vulnerable populations. Ultimately, this study contributes to the ongoing discourse on global migration governance, offering insights into how national policies can evolve to better protect refugees while navigating political realities.